Norepinephrine modulation of heat dissipation in female rats lacking estrogen. (5th August 2022) - Fonseca, Cristina S.; Aquino, Nayara S. S.; Goncalves, Gleisy K. N.; Drummond, Lucas R.; Hipolito, Laisa T. M.; Silva, Juneo F.; Silva, Kaoma S. C.; Henriques, Patricia C.; Domingues, Talita E.; Lacerda, Ana C. R.; Guatimosim, Silvia; Coimbra, Candido C.; et al.
Abstract: Postmenopausal hot flushes are caused by lack of estradiol (E2) but their neuroendocrine basis is still poorly understood. Here, we investigated the interrelationship between norepinephrine and hypothalamic neurons, with emphasis on kisspeptin neurons in the arcuate nucleus (ARC), as a regulatory pathway in the vasomotor effects of E2. Ovariectomized (OVX) rats displayed increased tail skin temperature (TST), and this increase was prevented in OVX rats treated with E2 (OVX + E2). Expression of Fos in the hypothalamus and the number of ARC kisspeptin neurons coexpressing Fos were increased in OVX rats. Likewise, brainstem norepinephrine neurons of OVX rats displayed higher Fos immunoreactivity associated with the increase in TST. In the ARC, the density of dopamine‐ß‐hydroxylase (DBH)‐immunoreactive (ir) fibers was not altered by E2 but, importantly, DBH‐ir terminals were found in close apposition to kisspeptin cells, revealing norepinephrine inputs to ARC kisspeptin neurons. Intracerebroventricular injection of the α2‐adrenergic agonist clonidine (CLO) was used to reduce central norepinephrine release, confirmed by the decreased 3‐methoxy‐4‐hydroxyphenylglycol/norepinephrine ratio in the preoptic area and ARC. Accordingly, CLO treatment in OVX rats reduced ARC Kiss1 mRNA levels and TST to the values of OVX + E2 rats. Conversely, CLO stimulated Kiss1 expression in the anteroventral periventricular nucleus (AVPV) and increased luteinizing hormone secretion. These findings provide evidence that augmented heat dissipation in OVX rats involves the increase in central norepinephrine that modulates hypothalamic areas related to thermoregulation, including ARC kisspeptin neurons. This neuronal network is suppressed by E2 and its imbalance may be implicated in the vasomotor symptoms of postmenopausal hot flushes. Abstract : The kisspeptin neurons in the arcuate nucleus of female ratsreceive norepinephrine inputs. This is a possible neuroendocrine pathway for the noradrenergic modulation of the increased heat dissipation in females lacking estrogen.